تمثلات العمال للعمل النقابي في الجزائر: دراسة سوسيولوجية بمؤسسة الإسمنت بولاية سعيدة - براهمي، محمد; حاج مراد، مولاي (جامعة مصطفى اسطمبولي - كلية العلوم الإنسانية والاجتماعية, 2022)
مرت الحركة النقابية في الجزائر بظروف سوسيوتاريخية ساهمت في تشكيل المعالم الأساسية للنشاط النقابي في الجزائر. حيث تميزت البوادر الأولى للنشأة بالصعوبة من جانب والبطء من جانب آخر، إلا أن الوعي المهني لدى العمال الجزائريين أدى إلى ازدهار النشاط النقابي وإحداث قفزة نوعية في تاريخ الحركة العمالية الجزائرية، وتأتي الدراسة الراهنة لمعرفة تمثلات العمال لأداء التنظيم النقابي (الاتحاد العام للعمال الجزائريين) في ظل التغيرات السوسيو - اقتصادية. The trade union movement in Algeria went through historical sociological conditions that contributed to shaping the main features of trade union activity in Algeria. Where the first signs of growing up were marked by difficulty on one side and slow on the other side. However, the occupational awareness of the Algerian workers has led to a flourishing trade union activity and a qualitative leap in the history of the Algerian labor movement, and the current study comes to know the representations of workers to perform the trade union organization (the General Union of Algerian Workers) in light of socio-economic changes.
Keywords: الحركة العمالية -- علم الاجتماع -- الجزائر